The dynamics of job creation and destruction for university graduates : why a rising unemployment rate can be misleading - Cardoso, Ana Rute (2009)
A large matched employer–employee data set on the Portuguese economy is used to analyse gross job creation and job destruction for university graduates, compared to other groups of workers. Standard measures of gross job flows are computed, and variance decomposition is used to check whether idiosyncratic shocks or aggregate and sectoral shocks can account for the time variation in gross job flows, for schooling groups separately. Results indicate that the market for university graduates has expanded much more than that for undergraduates, and that idiosyncratic shocks are more relevant driving job flows for university graduates than for nongraduates. No support is therefore found for the pessimistic view that states that the expansion of higher education may have gone too far.